2018
DOI: 10.1038/s41593-018-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct mechanisms for experience-dependent homeostasis

Abstract: Models of firing rate homeostasis such as synaptic scaling and the sliding synaptic plasticity modification threshold predict that decreasing neuronal activity (e.g. by sensory deprivation) will enhance synaptic function. Manipulations of cortical activity during two forms of visual deprivation (dark exposure (DE) and binocular lid suture (BS)) revealed that, contrary to expectations, spontaneous firing in conjunction with loss of visual input is necessary to lower the threshold for Hebbian plasticity and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 55 publications
8
71
0
Order By: Relevance
“…While sensory deprivation is a venerable paradigm for inducing neocortical plasticity (Espinosa and Stryker, 2012;Gainey and Feldman, 2017), there has been a dearth of approaches for increasing, rather than decreasing, neocortical firing to study downward homeostatic plasticity. Prolonged dark exposure is one paradigm that has been proposed to induce homeostatic plasticity within V1 (Goel and Lee, 2007), but more recent work has shown that changes in mEPSC amplitude during dark exposure unfold via metaplastic rules that are distinct from those that induce synaptic scaling (Bridi et al, 2018). Dark exposure does not impact firing rates in V1 over the first day or so (Torrado Pacheco et al, 2019) and so would not be expected to induce synaptic scaling, and after longer dark exposure there is disagreement as to whether firing rates increase (Bridi et al, 2018) or decrease (Torrado Pacheco et al, 2019); in both studies these effects were subtle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sensory deprivation is a venerable paradigm for inducing neocortical plasticity (Espinosa and Stryker, 2012;Gainey and Feldman, 2017), there has been a dearth of approaches for increasing, rather than decreasing, neocortical firing to study downward homeostatic plasticity. Prolonged dark exposure is one paradigm that has been proposed to induce homeostatic plasticity within V1 (Goel and Lee, 2007), but more recent work has shown that changes in mEPSC amplitude during dark exposure unfold via metaplastic rules that are distinct from those that induce synaptic scaling (Bridi et al, 2018). Dark exposure does not impact firing rates in V1 over the first day or so (Torrado Pacheco et al, 2019) and so would not be expected to induce synaptic scaling, and after longer dark exposure there is disagreement as to whether firing rates increase (Bridi et al, 2018) or decrease (Torrado Pacheco et al, 2019); in both studies these effects were subtle.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged dark exposure is one paradigm that has been proposed to induce homeostatic plasticity within V1 (Goel and Lee, 2007), but more recent work has shown that changes in mEPSC amplitude during dark exposure unfold via metaplastic rules that are distinct from those that induce synaptic scaling (Bridi et al, 2018). Dark exposure does not impact firing rates in V1 over the first day or so (Torrado Pacheco et al, 2019) and so would not be expected to induce synaptic scaling, and after longer dark exposure there is disagreement as to whether firing rates increase (Bridi et al, 2018) or decrease (Torrado Pacheco et al, 2019); in both studies these effects were subtle. Even light re-exposure after 60 hr in the dark only elevates firing for ~20 minutes, not long enough to trigger slow forms of homeostatic plasticity (Torrado Pacheco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme alteration of activity using sensory deprivation and/or stimulation has been shown to induce homeostatic plasticity in vivo (Bridi et al, 2018;Desai et al, 2002;Glazewski et al, 2017;Goel and Lee, 2007;Hengen et al, 2013;Knogler et al, 2010;Kotak et al, 2005).…”
Section: Sensory Deprivation Induces a Homeostatic Response In The Bamentioning
confidence: 99%
“…The change in NMDAR composition and function predicts that the threshold for 285Hebbian synaptic plasticity is lowered by DE(Cooper and Bear, 2012). Indeed, following 286 3 days of DE, spontaneous activity is sufficient to induce an GluN2B-dependent 287 potentiation of excitatory synapse strength in V1(Bridi et al, 2018). However, this 288 increase in excitability does not appear to induce MMP2/9 activity, as no change in 289 biomarker expression or ECM integrity is observed following prolonged DE alone 290(Murase et al, 2017).…”
mentioning
confidence: 99%